Calodium hepaticum: household clustering transmission and the finding of a source of human spurious infection in a community of the Amazon region. - Alessandra Queiroga Gonçalves; Carlos Ascaso; Ivanildes Santos; Paula Taquita Serra; Genimar Rebouças Julião; Patricia Puccinelli Orlandi (PLoS Neglected Tropical Diseases, 2012)
Background Calodium hepaticum (syn. Capillaria hepatica) is a worldwide helminth parasite of which several aspects of transmission still remain unclear. In the Amazon region, the mechanism of transmission based on the ingestion of eggs present in the liver of wild mammals has been suggested as the cause of the spurious infections described. We performed an epidemiological investigation to determine the incidence, risk of spurious infection and the dynamics of transmission of C. hepaticum in a community of the Brazilian Amazon. Methodology/principal findings Stool samples of 135 individuals, two dog feces and liver tissue from a peccary (captured and eaten by the residents) were analyzed by conventional microscopy. Dog feces were collected from the gardens of households presenting human cases of spurious C. hepaticum infections. Community practices and feeding habits related to the transmission of the parasite were investigated. The individual incidence of spurious infection was 6.7% (95% CI: 2.08-11.24). Cases of spurious infection were observed in 7.5% of the families and the household incidence was from 50% to 83.3%. The risk of spurious infection was 10-fold greater in persons consuming the liver of wild mammals (p = 0.02). The liver tissue of a peccary and one feces sample of a dog presented eggs of C. hepaticum. The consumption of the infected liver was the cause of the spurious infections reported in one household. Conclusions/significance This is the first identification of a source of spurious infection by C. hepaticum in humans and we describe a high rate of incidence in household clusters related to game liver alimentary habits. The finding of a dog feces contaminating peridomiciliary ground suggests the risk of new infections. We conclude that the mechanism of transmission based on the ingestion of liver is important for the dynamics of transmission of C. hepaticum in the studied area.